Mr. Selfridge. Season 3 [videorecording (DVD)] - Piven, Jeremy; Loftus, Aisling, 1990-; Cook, Ron, 1948- (PBS Distribution, 2015)
It's 1919, WWI has just ended, and Harry Selfridge is struggling with loss. After the death of his beloved Rose, he is making costly business mistakes. His empire is weakened, and he is vulnerable to his old enemy Lord Loxley.